IN DEPTH DESCRIPTION OF TWO ORGANIZATIONAL STRUCTURES - Yakubov Abdurashid; Tashmuxamedova Mariyam; Yusupova Yulduz; Nosirova Malikabonu (PEDAGOGS, 2024)
Abstract: Conceptualization of organizational structure is the manifestation of systematic thought. The organization is composed of elements, relations between elements and structure as a generality composing a unit. Structure is high combination of the relations between organizational elements forming existence philosophy of organizational activity. Systematic view of organization to structure shows that structure is composed of hard elements on one side and soft elements on the other side. The review of literature views structural relations from various aspects.